Great battles of WWII - Madacy Entertainment ([Canada] : Madacy Entertainment, 2002)
Collection of 4 story from World War II, includes the story of the Nazi defeat on the Western front, Hitler stood, , a tornado war, andbattle of Russia
D-Day: Battle for the beach -- Battle of Britain -- Battle of Russia -- Battle of the Vulga
Bonus DVD features: Animated scene index, interactive trivia game, biography, aircraft page, WWII medals
DVD format
Dolby digital
Keywords: World War, 1939-1945; World War, 1939-1945 -- Campaigns